The Effectiveness of Instagram @folkative Social Media as a Means of Information for the Young Generation - Nisa Aulia Maharani; Faja Faradila; Wahyunengsih Wahyunengsih (Jurnal Visi Komunikasi, 2022)
The internet, which is a new medium, is a sign of a new period, namely the existence of interactive technology and network communication, especially in cyberspace, which will change society (Littlejohn & Foss, 2014). With the internet, information is becoming easier to spread and get anytime and anywhere. One of the new mediums is Instagram. Instagram is a social media platform that is used to send information to the public quickly. One of the things uploaded on Instagram is information about the latest news on the @folkative account. This study aims to determine whether the @folkative Instagram account is effective as a means of information for the younger generation. The method used in this study is a qualitative one with data sources from questionnaires. The conclusion from the research results obtained is that the use of social media like Instagram as a means of information for the younger generation has been effective.